The mortars of Giotto's Bell Tower (Florence, Italy): raw materials and technologies. (18th January 2021) - Cantisani, Emma; Calandra, Sara; Barone, Serena; Caciagli, Samuele; Fedi, Mariaelena; Garzonio, Carlo Alberto; Liccioli, Lucia; Salvadori, Barbara; Salvatici, Teresa; Vettori, Silvia
Highlights: The first multi-analytical analyses of mortars of Giotto's Bell Tower (Florence). Knowledge of building technologies and raw materials used in the past. The use of natural hydraulic lime to obtain mortars with good performance. Radiocarbon dating of mortars. Abstract: Giotto's Bell Tower is known as one of the most important religious buildings of the 14th century in Florence (Italy). Its different construction phases have been well documented over time. The possibility of analyzing mortars collected from different construction phases, allowed us a complete chemical, mineralogical, petrographic, physical and mechanical characterization of these materials, improving the knowledge of building technologies and raw materials used at different times. In addition, knowing the approximate time of production of the mortar samples, it was possible to verify if they are suitable for radiocarbon dating.